Laminated Molded Body
Patent Information
- Application Number
- JP2021044883
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-03-18
AI Technical Summary
【0013】 本発明によれば、変性ポリエステル系エラストマーを含む接着樹脂層とガスバリア性樹脂層とを含む積層成形体であって、高い接着性と優れた溶剤耐久性を兼ね備える積層成形体が提供される。
Smart Images

Figure 0007600798000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated molded article comprising an adhesive resin layer containing a modified polyester elastomer and a gas barrier resin layer. [Background technology]
[0002] Laminated molded products made of gas barrier resins, such as ethylene-vinyl alcohol copolymers and polyamide resins, and polyolefin resins, are widely used in the food packaging field for containers such as films, bottles, and cups, and in the non-food field for industrial piping and hoses, tubes for transporting beverages and medicines, automobile parts, etc., due to their excellent mechanical properties, safety in food applications, and gas barrier properties against water vapor, oxygen, etc. When it is desired to impart aroma preservation, rigidity, heat resistance, cold resistance, surface printability, etc. to such laminated molded products, polyester resins are used instead of polyolefin resins, or a polyester resin layer is further laminated onto the laminated products.
[0003] Since ethylene-vinyl alcohol copolymers and polyamide resins have poor adhesion to polyester resins, a technique for laminating them by providing an adhesive layer made of an adhesive resin composition is known. For example, Patent Document 1 describes an adhesive resin composition made of a modified polyester elastomer having a polyalkylene ether glycol segment content of 58 to 73% by weight.
[0004] On the other hand, in food packaging containing oily contents, industrial hoses, drug delivery tubes, automobile parts, etc. that come into contact with chemicals and solvents in the usage environment, there is a problem that oil, chemicals, and solvents migrate to the interface of each resin layer of the laminated molded product that constitutes them, causing peeling. In addition, in applications where the product is exposed to a solvent for a long period of time, the adhesive layer made of the adhesive resin composition may swell and deform due to the solvent, causing deformation and embrittlement of the laminated molded product. For this reason, an adhesive resin composition with excellent solvent resistance is required. Patent Document 2 describes that an adhesive layer made of a composition containing a modified polyethylene having a specific melt flow rate and density and an unmodified polyethylene has excellent initial adhesive strength and solvent durability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2002-155135 A [Patent Document 2] JP 2003-73506 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the adhesive resin composition described in Patent Document 1 has excellent adhesiveness, but has room for improvement in solvent durability, as shown in Comparative Examples 3 to 5 below.The adhesive resin composition described in Patent Document 2 has excellent solvent durability, but has insufficient adhesiveness, as shown in Comparative Example 6 below.
[0007] An object of the present invention is to provide a laminated molded article comprising an adhesive resin layer containing a modified polyester-based elastomer and a gas barrier resin layer, which has satisfactory adhesiveness and solvent resistance. [Means for solving the problem]
[0008] The present inventors have conducted intensive research to solve the above-mentioned problems, and have found that the above-mentioned problems can be solved by a laminate molded product comprising an adhesive resin layer and a gas barrier resin layer, the modified polyester-based elastomer being obtained by modifying a polyester-polyether block copolymer with an unsaturated carboxylic acid and / or a derivative thereof, the modified polyester-based elastomer containing a specific ratio of polyalkylene ether glycol segments, and have thus completed the present invention. That is, the present invention relates to the following.
[0009] [1] A laminated molded product comprising at least an adhesive resin layer containing a modified polyester-based elastomer and a gas barrier resin layer, the modified polyester-based elastomer being a modified polyester-based elastomer obtained by modifying a polyester-based elastomer consisting of a polyester-polyether block copolymer having a hard segment containing an aromatic polyester and a soft segment containing a polyalkylene ether glycol segment with an unsaturated carboxylic acid and / or a derivative thereof, and the content of the polyalkylene ether glycol segment in the modified polyester-based elastomer is 36 to 53 mass%.
[0010] [2] The laminated molded product according to [1], wherein the adhesive resin layer contains the modified polyester-based elastomer in an amount of 50 mass% or more relative to the total components of the adhesive resin layer.
[0011] [3] The laminated molded product according to [1] or [2], wherein the gas barrier resin layer is a resin layer containing an ethylene-vinyl alcohol copolymer as a main component.
[0012] [4] The laminate molded product according to any one of [1] to [3], further comprising a polyester-based resin layer, the adhesive resin layer being disposed between the gas barrier resin layer and the polyester resin layer. Effect of the Invention
[0013] According to the present invention, there is provided a laminate molded article including an adhesive resin layer containing a modified polyester-based elastomer and a gas barrier resin layer, the laminate molded article having both high adhesion and excellent solvent resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below. However, the following description is an example of an embodiment of the present invention, and the present invention is not limited to the contents of the following description as long as it does not go beyond the gist of the present invention. The present invention can be modified and implemented as desired without departing from the gist of the present invention. In the present invention, when "~" is used to express a numerical value or a physical property value, the values before and after the "~" are included.
[0015] In the present invention, the density, melting point, hardness, melt flow rate (MFR), and content of polyalkylene ether glycol segment of the resin are values measured as follows.
[0016] <density> The density is measured by the underwater displacement method in accordance with JIS K7112.
[0017] <Melting point> The melting point is measured using a differential scanning calorimeter (DSC). Specifically, the temperature is first raised to 300°C to remove the thermal history, then the temperature is lowered to 40°C at a rate of 10°C / min, and then the temperature is raised again at a rate of 10°C / min to measure the melting point. The unit is °C.
[0018] <Hardness> This is the JIS-D hardness measured using a durometer in accordance with JIS K6253 (D hardness).
[0019] <mfr> The MFR (melt flow rate) of the polyester elastomer and modified polyester elastomer described below is measured at 230°C, with a load of 2.16 kg, for 10 minutes in accordance with JIS K7210. During the measurement, the polyester elastomer and modified polyester elastomer are vacuum dried in pellet form at 100°C for 4 hours to remove the moisture contained therein. The MFR of modified polyethylene is measured in accordance with JIS K7210 under conditions of a temperature of 190°C, a load of 2.16 kg, and a time of 10 minutes.
[0020] <Polyalkylene ether glycol segment content in modified polyester elastomer> The content of polyalkylene ether glycol segments in the modified polyester elastomer was measured by dissolving the sample in a mixed solvent of deuterated chloroform / hexafluoroisopropanol and measuring the content at room temperature using a nuclear magnetic resonance apparatus (AVANCE400 spectrometer manufactured by Bruker). 1 The H NMR spectrum is measured and the chemical shifts of the hydrogen spectrum are used as the basis for the calculation. When two or more types of modified polyester-based elastomers are used, each modified polyester-based elastomer is used as the subject sample, and each is measured in the same manner as above to calculate the polyalkylene ether glycol segment content, which can then be calculated proportionally based on the blending mass ratio of each modified polyester-based elastomer. Theoretically, the content of the polyalkylene ether glycol segment in the modified polyester elastomer is the same as the content of the polyalkylene ether glycol segment in the polyester elastomer before modification, i.e., it can be considered that there is no change in the content of the polyalkylene ether glycol segment before and after modification.
[0021] The laminated molded product of the present invention is a laminated molded product including at least an adhesive resin layer containing a modified polyester-based elastomer and a gas barrier resin layer, the modified polyester-based elastomer being obtained by modifying a polyester-based elastomer consisting of a polyester-polyether block copolymer consisting of a hard segment containing an aromatic polyester and a soft segment containing a polyalkylene ether glycol segment with an unsaturated carboxylic acid and / or a derivative thereof, and the content of the polyalkylene ether glycol segment in the modified polyester-based elastomer is 36 to 53 mass%. Hereinafter, the modified polyester-based elastomer contained in the adhesive resin layer of the present invention will be referred to as the "modified polyester-based elastomer of the present invention," and the polyester-based elastomer before modification will be simply referred to as the "polyester-based elastomer" or "component (A)." Furthermore, the unsaturated carboxylic acid and / or its derivative used to modify the polyester elastomer may be referred to as "component (B)", and the radical generator used in the modification treatment may be referred to as "component (C)".
[0022] The modified polyester-based elastomer of the present invention is obtained by modifying a polyester-based elastomer, which is a polyester-polyether block copolymer consisting of a hard segment containing an aromatic polyester and a soft segment containing a polyalkylene ether glycol segment, with an unsaturated carboxylic acid and / or a derivative thereof.
[0023] In the present invention, the modification refers to graft modification of the polyester elastomer with an unsaturated carboxylic acid and / or a derivative thereof, terminal modification and modification by transesterification reaction, modification by decomposition reaction, etc. Specifically, the site where the unsaturated carboxylic acid and / or a derivative thereof is bonded may be a terminal functional group or an alkyl chain portion, particularly a terminal carboxyl group, a terminal hydroxyl group, and a carbon atom at the α-position or β-position with respect to the ether bond of the polyalkylene ether glycol segment. In particular, it is presumed that many are bonded to the α-position with respect to the ether bond of the polyalkylene ether glycol segment.
[0024] When a polyester elastomer is modified with an unsaturated carboxylic acid and / or its derivative, a modified polyester elastomer is usually obtained as a composition containing a modified polyester elastomer modified with the polyester elastomer, an unmodified polyester elastomer, the unsaturated carboxylic acid and / or its derivative used in the modification, a radical generator described below, etc. The modified polyester elastomer of the present invention means a modified polyester elastomer composition obtained by such a modification reaction and containing residues of the unmodified polyester elastomer, the unsaturated carboxylic acid and / or its derivative, etc. In addition, the modified polyester-based elastomer of the present invention may be a mixture of a modified polyester-based elastomer obtained by modifying a polyester-based elastomer and an unmodified polyester-based elastomer, as long as the content of the polyalkylene ether glycol segment specified in the present invention, and preferably the suitable acid modification rate described below, is satisfied.
[0025] [mechanism] The adhesive resin layer according to the present invention contains a modified polyester elastomer, and therefore can have sufficient adhesion to a gas barrier resin layer, particularly to an ethylene-vinyl alcohol copolymer or a polyamide resin. In addition, since the modified polyester elastomer according to the present invention has a polyester as the main skeleton, it has high compatibility with polyester resins and high adhesion. In addition, when the content of the polyalkylene ether glycol segment in the modified polyester elastomer of the present invention is 36 to 53 mass%, it is possible to achieve both adhesiveness and solvent resistance. This is presumably because a large amount of unsaturated carboxylic acid and / or its derivative is bonded to the polyalkylene ether glycol segment in the modified polyester elastomer due to modification. That is, if the modified polyester elastomer contains a sufficient amount of polyalkylene ether glycol segment of 36 mass% or more, the degree of modification (content of unsaturated carboxylic acid component contained in the modified polyester elastomer) is high, and adhesiveness to the gas barrier resin can be sufficiently satisfied. On the other hand, when the content of the polyalkylene ether glycol segment in the modified polyester elastomer is 53 mass% or less and the remaining portion contains a sufficient amount of highly crystalline hard segments, the crystallinity of the modified polyester elastomer is high, and as a result, the solvent resistance is excellent.
[0026] [Polyester elastomer] The polyester elastomer according to the present invention is a polyester-polyether block copolymer comprising a hard segment containing an aromatic polyester and a soft segment containing a polyalkylene ether glycol. The content of the polyalkylene ether glycol segment in the polyester elastomer according to the present invention is 36 to 53% by mass, preferably 38 to 50% by mass, for the same reasons as in the modified polyester elastomer described below. As in the case of the modified polyester-based elastomer, when two or more kinds of polyester-based elastomers are used, even if some of the polyester-based elastomers have a polyalkylene ether glycol segment content outside the range of 35 to 53 mass%, it is acceptable as long as the overall polyalkylene ether glycol segment content is within the range of 36 to 53 mass%.
[0027] In addition, polyester elastomers have a density of 1.00 to 1.35 g / cm 3 Preferably, the density is 1.05 to 1.30 g / cm 3 More preferably, it is 1.10 to 1.25 g / cm 3 The density is correlated with the polyalkylene ether glycol content, and the higher the polyalkylene ether glycol content, the lower the density. That is, by setting the density to the lower limit or higher of the above range, it becomes easier to suppress the decrease in solvent resistance, and by setting the density to the upper limit or lower of the above range, it becomes easier to improve the adhesion to the gas barrier resin.
[0028] The polyester elastomer preferably has a melting point of 145 to 245° C., more preferably 160 to 230° C., and even more preferably 175 to 215° C. By setting the melting point to be equal to or higher than the lower limit of the above range, it becomes easier to prevent the heat resistance from decreasing in the usage environment, and by setting the melting point to be equal to or lower than the upper limit of the above range, it becomes easier to improve the co-extrusion moldability with gas barrier resins that are thermally deteriorated at high temperatures, such as ethylene-vinyl alcohol copolymers.
[0029] The polyester-based elastomer preferably has a D hardness (JIS-D hardness) of 10 to 80, more preferably 20 to 70, and even more preferably 40 to 60. When the JIS-D hardness is equal to or higher than the lower limit of the above range, the solvent resistance tends to be excellent, and when the JIS-D hardness is equal to or lower than the upper limit of the above range, the required flexibility tends to be easily maintained when the polyester-based elastomer is formed into a laminate such as a film or a tube.
[0030] In addition, the MFR of the polyester elastomer, measured in accordance with JIS K7210 under conditions of a temperature of 230°C, a load of 2.16 kg, and a time period of 10 minutes, is preferably 0.5 to 300 g / 10 min, more preferably 1 to 150 g / 10 min, and even more preferably 2 to 75 g / 10 min. When the MFR of the polyester elastomer is equal to or lower than the upper limit of the above range, the melt tension is increased and drawdown during molding is easily suppressed, whereas when the MFR is equal to or higher than the lower limit of the above range, deterioration of moldability, such as uneven thickness caused by insufficient fluidity, is easily suppressed.
[0031] A polyester-based elastomer consisting of a hard segment containing an aromatic polyester and a soft segment containing a polyalkylene ether glycol can usually be obtained by polycondensing an oligomer obtained by an esterification reaction or an ester exchange reaction using i) an aliphatic and / or alicyclic diol having 2 to 12 carbon atoms, ii) an aromatic dicarboxylic acid and / or an alkyl ester thereof, and iii) a polyalkylene ether glycol having a number average molecular weight of 400 to 6,000 as raw materials.
[0032] i) As the aliphatic and / or alicyclic diol having 2 to 12 carbon atoms, those usually used as raw materials for polyesters, particularly raw materials for polyester-based elastomers, can be used. For example, ethylene glycol, propylene glycol, trimethylene glycol, 1,4-butanediol, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol can be mentioned, among which 1,4-butanediol and ethylene glycol are preferred, and 1,4-butanediol is particularly preferred. These diols can be used alone or in a mixture of two or more kinds.
[0033] ii) As the aromatic dicarboxylic acid, those generally used as raw materials for polyesters, particularly raw materials for polyester elastomers, can be used, such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid. Among these, terephthalic acid and 2,6-naphthalenedicarboxylic acid are preferred, and terephthalic acid is particularly preferred. These dicarboxylic acids may be used in combination of two or more kinds. When an alkyl ester of an aromatic dicarboxylic acid is used, the dimethyl ester or diethyl ester of the above dicarboxylic acid is used. Dimethyl terephthalate and 2,6-dimethyl naphthalate are preferred.
[0034] iii) Examples of polyalkylene ether glycols include polyethylene glycol, poly(1,2 and 1,3-propylene ether) glycol, poly(tetramethylene ether) glycol, poly(hexamethylene ether) glycol, and poly(decamethylene ether) glycol. Among these, poly(tetramethylene ether) glycol is particularly preferably used.
[0035] The polyalkylene ether glycol generally has a number average molecular weight of 400 to 6,000, preferably 600 to 4,000, and more preferably 900 to 3,000. When the number average molecular weight is equal to or higher than the lower limit of the above range, the degree of modification by the unsaturated carboxylic acid and / or its derivatives can be easily controlled to a desired range, and sufficient adhesiveness tends to be easily exhibited. On the other hand, when the number average molecular weight is equal to or lower than the upper limit of the above range, phase separation in the system can be suppressed, and the deterioration of the physical properties of the obtained polymer tends to be suppressed. The "number average molecular weight" referred to here is measured by nuclear magnetic resonance (NMR) analysis. The polyalkylene ether glycol is used so that the content of the polyalkylene ether glycol segment in the polyester elastomer is 36 to 53% by mass, preferably 38 to 50% by mass.
[0036] In addition to the above components, a small amount of a trifunctional triol or tricarboxylic acid or an ester thereof may be copolymerized in the polyester elastomer, and further, an aliphatic dicarboxylic acid such as adipic acid or a dialkyl ester thereof may also be used as a copolymerization component.
[0037] As the polyester-based elastomer, commercially available products may be used, and examples of commercially available products include "TEFABLOCK (registered trademark)" manufactured by Mitsubishi Chemical Corporation, "PELPRENE (registered trademark)" manufactured by Toyobo Co., Ltd., and "HYTREL (registered trademark)" manufactured by DuPont-Toray Co., Ltd.
[0038] The polyester elastomer may be one type, or two or more types having different monomer compositions, physical properties, etc. may be subjected to modification with an unsaturated carboxylic acid and / or a derivative thereof. As described above, when two or more polyester elastomers are used, even if some of the polyester elastomers have a polyalkylene ether glycol segment content outside the range of 35 to 53 mass%, it is sufficient as long as the overall polyalkylene ether glycol segment content is within the range of 36 to 53 mass%.
[0039] [Unsaturated carboxylic acid and / or its derivative] The unsaturated carboxylic acid used to modify the polyester elastomer is preferably an α,β-ethylenically unsaturated carboxylic acid, such as acrylic acid, methacrylic acid, ethacrylic acid, maleic acid, fumaric acid, tetrahydrofumaric acid, itaconic acid, citraconic acid, crotonic acid, and isocrotonic acid. Examples of derivatives of unsaturated carboxylic acids include acid anhydrides and carboxylates of these unsaturated carboxylic acids, and may further include derivatives such as acid halides, amides, and imides. Of these derivatives, acid anhydrides are preferred.
[0040] As the unsaturated carboxylic acid and / or its derivative, maleic acid and / or its anhydride are particularly suitable. In addition, a plurality of these compounds may be used in combination. Furthermore, so-called vinyl silanes such as vinyltrimethoxysilane may be used in combination with the unsaturated carboxylic acid and / or its derivative.
[0041] [Radical generator] When the polyester elastomer is modified with an unsaturated carboxylic acid and / or a derivative thereof, a radical generator is usually used to carry out a radical reaction. Examples of the radical generator include peroxy esters, dialkyl peroxides, diacyl peroxides, hydroperoxides, and ketone peroxides. Of these, diacyl peroxides such as dibenzoyl peroxide and 2,5-dimethyl-2,5-di(t-butylperoxy)hexane are preferably used. These radical generators may be appropriately selected depending on the type of polyester elastomer, the type of unsaturated carboxylic acid and / or its derivative, and the modification conditions, and two or more types may be used in combination. The radical generator may be added by dissolving it in an organic solvent or the like.
[0042] [Method of manufacturing modified polyester elastomer] The modified polyester elastomer of the present invention may be produced by any known method, such as a melt-kneading reaction method, a solution reaction method, or a suspension dispersion reaction method, but the melt-kneading reaction method is usually preferred.
[0043] In the case of the melt-kneading reaction method, the components (A) to (C) are mixed uniformly in a predetermined mixing ratio and then melt-kneaded. A Henschel mixer, ribbon blender, V-type blender, or the like can be used for mixing, and a single-screw or twin-screw extruder, roll, Banbury mixer, kneader, Brabender mixer, or the like can be usually used for melt-kneading. The melt kneading is carried out at a temperature of usually 100°C or higher, preferably 120°C or higher, more preferably 150°C or higher, and usually 300°C or lower, preferably 280°C or lower, more preferably 250°C or lower, so as to prevent thermal degradation of the resin.
[0044] The amount of the unsaturated carboxylic acid and / or its derivative used for modification as component (B) is usually 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and usually 10 parts by mass or less, preferably 5 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the polyester elastomer as component (A). By setting the amount of the unsaturated carboxylic acid and / or its derivative to be equal to or more than the lower limit, sufficient modification can be easily performed, and by setting the amount to be equal to or less than the upper limit, it is not only economical but also easy to prevent the unsaturated carboxylic acid and / or its derivative that did not contribute to the modification from acting as an impurity and reducing the adhesiveness.
[0045] The amount of the radical generator of component (C) is usually 0.001 parts by mass or more, preferably 0.005 parts by mass or more, more preferably 0.01 parts by mass or more, and usually 4 parts by mass or less, preferably 3 parts by mass or less, more preferably 2 parts by mass or less, based on 100 parts by mass of the polyester elastomer of component (A). When the amount of the radical generator is more than the lower limit, the modification reaction is easily caused, and when the amount is less than the lower limit, the material strength is prevented from being significantly reduced due to the promotion of the reduction in molecular weight (reduction in viscosity) of component (A). That is, in this modification reaction, a graft polymerization reaction in which component (B) an unsaturated carboxylic acid and / or its derivative is added to component (A) mainly occurs, but a decomposition reaction also occurs, and the molecular weight of the resulting modified product is reduced due to the decomposition, resulting in a reduction in material strength. If the amount of the radical generator used is too large, the graft polymerization reaction is easily caused, but at the same time, the decomposition reaction leading to such a reduction in molecular weight is also easily caused, which is not preferable.
[0046] The product obtained by this modification reaction can be used as the modified polyester elastomer of the present invention as it is for forming an adhesive resin layer, as described later.
[0047] [Polyalkylene ether glycol segment content in modified polyester elastomer] The content of the polyalkylene ether glycol segment in the modified polyester elastomer of the present invention is 36-53% by mass. When the content of the polyalkylene ether glycol segment in the modified polyester elastomer is 36-53% by mass, the adhesiveness and solvent resistance can be satisfied when the modified polyester elastomer is used as an adhesive resin layer. When the content of the polyalkylene ether glycol segment in the modified polyester elastomer exceeds the upper limit of the above range, the crystallinity tends to decrease and the solvent resistance tends to be poor. When the content of the polyalkylene ether glycol segment in the modified polyester elastomer is less than the lower limit of the above range, the low-temperature impact resistance and the adhesiveness to ethylene-vinyl alcohol copolymers and polyamide resins tend to decrease. From this viewpoint, the lower limit of the content of the polyalkylene ether glycol segment in the modified polyester elastomer of the present invention is preferably 38% by mass or more. On the other hand, the upper limit of the content of the polyalkylene ether glycol segment in the modified polyester elastomer of the present invention is preferably 50% by mass or less.
[0048] Here, the content of the polyalkylene ether glycol segment in the modified polyester elastomer refers to the content of the polyalkylene ether glycol segment in the entire modified polyester elastomer. That is, for example, when two or more modified polyester elastomers are mixed and used, even if one of them has a polyalkylene ether glycol segment content outside the range of 36 to 53 mass%, it is acceptable as long as the polyalkylene ether glycol segment content of the modified polyester elastomer as a mixture is within the range of 35 to 53 mass%.
[0049] [Acid modification rate of modified polyester elastomer] The modified polyester elastomer of the present invention may be produced by using an unsaturated carboxylic acid and / or its derivative and a radical generator in the above-mentioned suitable blending amount relative to the polyester elastomer, and the acid modification rate is not particularly limited, but is preferably 0.01 to 8. If the acid modification rate is equal to or higher than the lower limit of the above range, sufficient adhesion to the gas barrier resin layer can be obtained. If the acid modification rate is equal to or lower than the upper limit of the above range, discoloration due to the unsaturated carboxylic acid and / or its derivative can be suppressed. The lower limit of the acid modification rate is more preferably 0.1 or more, even more preferably 0.15 or more, and particularly preferably 0.16 or more. The upper limit of the acid modification rate is more preferably 4 or less, and even more preferably 0.8 or less. The acid modification rate of the modified polyester elastomer is measured and calculated by the method described in the Examples section below.
[0050] [Adhesive resin layer] The adhesive resin layer according to the present invention contains the modified polyester elastomer of the present invention in an amount of preferably 50% by mass or more, more preferably 55% by mass or more, and even more preferably 60% by mass or more, based on the total components of the adhesive resin layer. If the content of the modified polyester elastomer is equal to or more than the lower limit, the adhesion to the gas barrier resin layer and the solvent resistance can be sufficiently increased. The upper limit of the content of the modified polyester elastomer is not particularly limited, and may be 100% by mass.
[0051] In addition to the modified polyester elastomer of the present invention, the adhesive resin layer of the present invention may contain any other components (hereinafter, sometimes referred to as other components) depending on the purpose, as long as the effects of the present invention are not significantly hindered. The other components may be used alone or in any combination and ratio of two or more.
[0052] Specifically, the other components include resin components other than the modified polyester elastomer of the present invention, rubber components (polyester resins such as polyethylene terephthalate and polybutylene terephthalate, styrene resins such as polystyrene, polyolefin resins, and acrylic / methacrylic resins such as polymethyl methacrylate resins), heat stabilizers, weather stabilizers (antioxidants, light stabilizers, ultraviolet absorbers, etc.), flame retardants, antiblocking agents, slip agents, antistatic agents, fillers (inorganic and / or organic fillers, etc.), processing aids, plasticizers such as paraffin oil, crystal nucleating agents, impact modifiers, compatibilizers, neutralizers for catalyst residues, carbon black, colorants (pigments, dyes, etc.), antifogging agents, crosslinking agents, crosslinking aids, chain extenders, dispersants, antibacterial agents, antiviral agents, fluorescent whitening agents, and other various additives. Among these, it is preferable to add at least one of various antioxidants such as phenols, phosphites, thioethers, and aromatic amines. When these antioxidants are used, their content is not limited, but is usually 0.01 mass% or more, preferably 0.05 mass% or more, and usually 5 mass% or less, preferably 2 mass% or less, based on all components constituting the adhesive resin layer.
[0053] [Gas barrier resin layer] The gas barrier resin layer according to the present invention is preferably a resin layer mainly composed of an ethylene-vinyl alcohol copolymer. The ethylene-vinyl alcohol copolymer is produced by saponifying an ethylene-vinyl acetate copolymer in the presence of alcohol. As the ethylene-vinyl alcohol copolymer constituting the gas barrier resin layer, an ethylene-vinyl acetate copolymer having an ethylene content of preferably 15 to 65 mol %, more preferably 20 to 50 mol %, which is saponified to a degree of saponification of preferably 50% or more, more preferably 90% or more, is preferably used. Commercially available examples of such ethylene-vinyl alcohol copolymers include "Soarnol (registered trademark)" manufactured by Mitsubishi Chemical Corporation, "Eval (registered trademark)" manufactured by Kuraray Co., Ltd., and "Evasin" manufactured by Chang Chun Group.
[0054] The gas barrier resin layer may contain only one type of ethylene-vinyl alcohol copolymer, or may contain two or more types with different saponification degrees, monomer compositions, etc., but the gas barrier resin layer preferably contains ethylene-vinyl alcohol copolymer as the main component in an amount of usually 50% by mass or more, particularly 65 to 100% by mass, and especially 75 to 100% by mass. When the content of the ethylene-vinyl alcohol copolymer in the gas barrier resin layer is equal to or higher than the above lower limit, excellent gas barrier properties are obtained.
[0055] Components other than the ethylene-vinyl alcohol copolymer that may be contained in the gas barrier resin layer are not particularly limited, and examples thereof include resin components such as polyolefin resins, styrene resins, acrylic / methacrylic resins, etc., and various additives such as heat stabilizers, weather stabilizers (antioxidants, light stabilizers, ultraviolet absorbers, etc.), flame retardants, antiblocking agents, slip agents, fillers (inorganic and / or organic fillers, etc.), processing aids, plasticizers such as paraffin oil, crystal nucleating agents, impact improvers, compatibilizers, neutralizers for catalyst residues, and colorants (pigments, dyes, etc.).
[0056] [Polyester resin layer] The laminated molded product of the present invention may further include a layer of a polyester-based resin in order to impart functionality such as aroma preservation, rigidity, heat resistance, cold resistance, surface printability, etc. The polyester-based resin is produced by dehydration condensation of a polyvalent carboxylic acid and a polyalcohol, and examples of the polyester-based resin include those obtained by polycondensation of a dicarboxylic acid and a diol.
[0057] The carboxylic acid is not particularly limited, but examples thereof include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, diphenyl ether-4,4-dicarboxylic acid, and naphthalene-1,4- or 2,6-dicarboxylic acid; aliphatic dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, sebacic acid, and undecadicarboxylic acid; and alicyclic dicarboxylic acids such as hexahydroterephthalic acid.
[0058] The diol is not particularly limited, but examples thereof include alicyclic glycols such as ethylene glycol, propylene glycol, 1,4-butanediol, and neopentyl glycol, alicyclic glycols such as cyclohexanedimethanol, and aromatic dihydroxy compounds such as bisphenol A.
[0059] Examples of the polyester resin include polyethylene terephthalate (PET), PET copolymer, polybutylene terephthalate, polyethylene naphthalate, polycyclohexyne terephthalate, and polyester elastomer. These polyester resins can be used alone or in the form of a mixture of multiple polyester resins.
[0060] [Other layers] The laminated molded product of the present invention may further have other layers in addition to those described above. Examples of the other layers include layers made of resins other than the constituent resins of the adhesive resin layer, gas barrier resin layer, and polyester-based resin layer described above, and the substrate layer described below.
[0061] The resin constituting the layer made of other resins is not limited, and specific examples thereof include the resins listed as other components in the adhesive resin layer described above, polyamide-based resins such as nylon 66 and nylon 11, cyclic polyolefin resins, polyvinyl chloride, polyvinylidene chloride, and thermoplastic resins such as polycarbonate-based resins, but polyolefin-based resins and polyamide-based resins are preferred from the viewpoint of excellent co-extrudability with the modified polyester-based elastomer of the present invention.
[0062] In addition, since the adhesive resin layer containing the modified polyester-based elastomer of the present invention has excellent adhesion and solvent resistance, it can also be bonded to a base material layer such as a metal and / or resin sheet via this adhesive resin layer.
[0063] The form of the substrate layer is not limited to a film or a sheet, and may be a woven fabric or a nonwoven fabric. The substrate layer may be a single-layer structure or a multi-layer structure. The method for producing the multi-layer substrate is not particularly limited, and may include a co-extrusion film method, a dry lamination method, a wet lamination method, a hot melt lamination method, an extrusion lamination method, a thermal lamination method, etc.
[0064] In the laminate molded product of the present invention, any layer may be provided in addition to the adhesive resin layer containing the modified polyester-based elastomer of the present invention, the gas barrier resin layer, the polyester-based resin layer, the layer of other resins, and the base layer made of the above-mentioned metal or the like.
[0065] [Laminated molded body] The laminated molded product of the present invention is a laminated molded product containing an adhesive resin layer containing the modified polyester-based elastomer of the present invention and a gas barrier resin layer, and is preferably a laminated molded product having two or more layers laminated therein. Among them, it is preferable to have a gas barrier resin layer mainly composed of an ethylene-vinyl alcohol copolymer and, if necessary, the above-mentioned polyester-based resin layer. In particular, a laminated molded product having a polyester-based resin layer, an adhesive resin layer containing the modified polyester-based elastomer of the present invention, and a gas barrier resin layer laminated in this order is preferably used. In this case, for example, a laminated molded product having two or more layers laminated therein, such as a polyester-based resin layer / adhesive resin layer / gas barrier resin layer / adhesive resin layer / polyester-based resin layer, may be used.
[0066] The laminated molded article of the present invention may also be a laminated molded article having three or more layers, each having a layer of the other resin and / or metal described above. The laminated molded article of the present invention may be in the form of a laminated film, a laminated sheet, a laminated tube, etc. Here, the terms "film" and "sheet" both mean planar molded articles and have the same meaning.
[0067] The total thickness of the laminated molded product of the present invention is not particularly limited and can be appropriately adjusted depending on the application. The total thickness of the laminated molded product of the present invention is preferably 20 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more, and is preferably 10 mm or less, more preferably 6 mm or less, and even more preferably 1 mm or less. By having the thickness within the above range, it becomes easy to manufacture a laminated molded product without wrinkles or cracks.
[0068] The thickness of the adhesive resin layer containing the modified polyester-based elastomer of the present invention is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more, and is preferably 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.1 mm or less. The thickness of the gas barrier resin layer is generally 0.002 to 1 mm. The thickness of the polyester resin layer is generally 0.01 to 3 mm.
[0069] [Method of manufacturing laminated molded body] The laminated molded article of the present invention can be produced by various conventionally known methods. For example, the laminated molded article may be produced by a co-extrusion method in which individual molten resins melted in an extruder are fed into a multi-layer die and laminated in the die to produce an inflation film, cast film, sheet, tube, pipe, or bottle, or by co-injection molding in which individual molten resins are sequentially injected into the same die, or by co-extrusion lamination of an unstretched test tube-shaped parison or the like. EXAMPLES
[0070] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the invention. The values of various production conditions and evaluation results in the following examples are meant as preferred upper or lower limit values in the embodiment of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values and the values of the following examples or values of the examples.
[0071] 〔raw materials〕 The raw materials used in the production of laminated molded bodies in the following Examples and Comparative Examples are as follows.
[0072] [Adhesive resin layer] <Component (A)> A-1: Polyester elastomer A polyester-polyether block copolymer having polybutylene terephthalate as a hard segment and polytetramethylene ether glycol having a number average molecular weight of 1,000 as a soft segment, the polyester-based elastomer (density: 1.16 g / cm) having a polytetramethylene ether glycol segment content of 45% by mass in the copolymer. 3 , melting point: 189.9°C, JIS-D hardness: 43, MFR: 21g / 10min) were used. A-2: Polyester elastomer A polyester-polyether block copolymer having polybutylene terephthalate as a hard segment and polytetramethylene ether glycol having a number average molecular weight of 1,000 as a soft segment, the polyester-based elastomer (density: 1.20 g / cm) having a polytetramethylene ether glycol segment content of 32 mass% in the copolymer. 3 , melting point: 205.1°C, JIS-D hardness: 54, MFR: 22g / 10min) were used. A'-1: Polyester elastomer A polyester-polyether block copolymer having polybutylene terephthalate as a hard segment and polytetramethylene ether glycol having a number average molecular weight of 2,000 as a soft segment, the polyester-based elastomer (density: 1.07 g / cm) having a polytetramethylene ether glycol segment content of 73 mass% in the copolymer. 3 , melting point: 160.1°C, JIS-D hardness: 24, MFR: 20g / 10min) were used. A'-2: Polyester elastomer A polyester-polyether block copolymer having polybutylene terephthalate as a hard segment and polytetramethylene ether glycol having a number average molecular weight of 2,000 as a soft segment, the polyester-based elastomer (density: 1.10 g / cm) having a polytetramethylene ether glycol segment content of 64 mass% in the copolymer. 3 , melting point: 186.1°C, JIS-D hardness: 31, MFR: 21g / 10min) were used. A'-3: Polyester elastomer A polyester-polyether block copolymer having polybutylene terephthalate as a hard segment and polytetramethylene ether glycol having a number average molecular weight of 1,000 as a soft segment, the polyester-based elastomer (density: 1.10 g / cm) having a polytetramethylene ether glycol segment content of 61% by mass in the copolymer. 3 , melting point: 160.6°C, JIS-D hardness: 38, MFR: 17g / 10min) were used. A'-4: Polyester elastomer A polyester-polyether block copolymer having polybutylene terephthalate as a hard segment and polytetramethylene ether glycol having a number average molecular weight of 1,000 as a soft segment, the polyester-based elastomer (density: 1.26 g / cm) having a polytetramethylene ether glycol segment content of 20 mass% in the copolymer. 3 , melting point: 220.0°C, JIS-D hardness: 60, MFR: 60g / 10min) were used.
[0073] <Ingredient (B)> B: Unsaturated carboxylic acid anhydride "Maleic anhydride (special grade reagent)" (particle size 5 to 10 mm) manufactured by Wako Pure Chemical Industries, Ltd. was crushed in a small mixer to a particle size of 1 mm or less and used.
[0074] <Ingredient (C)> C: Benzoyl peroxide "Niper (registered trademark) BMTK-40" manufactured by Nippon Oil & Fats Corporation was used.
[0075] <Additives> X: A phenolic antioxidant "Irganox 1010 (registered trademark)" manufactured by BASF was used.
[0076] [Adhesive resin layer not containing modified polyester elastomer] Acid-modified polyethylene Mitsubishi Chemical Corporation's "Modic (registered trademark) H501E" (MFR: 0.8 g / 10 min, density: 0.92 g / cm 3 ) was used.
[0077] [Gas barrier resin layer] Ethylene-vinyl alcohol copolymer (EVOH) "EVAL (registered trademark) L171B" manufactured by Kuraray Co., Ltd. was used.
[0078] [Polyester resin] Mitsubishi Chemical Corporation's "TEFABLOCK (registered trademark) B1921" was used.
[0079] [Evaluation method] In the examples and comparative examples, physical properties were evaluated by the methods described below.
[0080] [Polyalkylene ether glycol segment content in polyester elastomer and modified polyester elastomer] The polyalkylene ether glycol content in the polyester elastomer and the modified polyester elastomer was measured according to the method described above.
[0081] [Acid denaturation rate] The acid modification rate is the content of unsaturated carboxylic acid components in the modified polyester elastomer when measured with an infrared spectrometer (JASCOFT / IR610, manufactured by JASCO Corporation). The acid modification rate is the absorption (1900-1600 cm) specific to unsaturated carboxylic acid and / or its derivatives in a sample obtained by press-molding pellets of the modified polyester elastomer into a sheet having a thickness of 20-50 μm at 230° C. -1 ) and the absorption characteristic of aromatic rings in the hard segments (1000-800 cm -1 ) was measured.
[0082] [Measurement of swelling degree] The obtained modified polyester elastomer or comparative acid-modified polyethylene was injection molded at a melt temperature of 240°C and a mold temperature of 40°C to obtain test pieces with a length of 80 mm, a width of 10 mm and a thickness of 4 mm. These were then immersed in a mixed liquid of equal amounts (volume) of isooctane / toluene at 60°C for 168 hours, and the swelling degree (%) was calculated using the following formula. Swelling degree (%) = [{W1-W0} / W0] x 100 Weight of test piece before immersion: W0(g) Weight of test piece after immersion: W1 (g) If the swelling degree is 40% or less, deformation and embrittlement of the laminated molded body can be suppressed and it was evaluated as being practical.
[0083] [Measurement of adhesive strength of laminated molded body] Generally, an interlaminar strength of 2N / 15mm or more is considered to be sufficient for practical use. <Adhesive strength before immersion in solvent> The five-layer film obtained in each example was cut into a 15 mm wide strip parallel to the molding direction to prepare a test piece, and a T-peel test was performed at a speed of 300 mm / min in a constant temperature atmosphere of 23°C to measure the adhesive strength. Here, the adhesive strength in Examples 1 to 3 and Comparative Examples 1 to 5 is the adhesive strength at the interface between the ethylene-vinyl alcohol copolymer layer and the adhesive resin layer. The adhesive strength in Comparative Example 6 is the adhesive strength at the interface between the polyester resin layer and the adhesive resin layer. <Adhesive strength after immersion in solvent> For the five-layer film obtained in each example, a strip-shaped test piece prepared in the same manner as above was immersed in a mixture of equal amounts (volume) of isooctane / toluene at 60°C for 168 hours, and within 5 minutes after removal, a T-peel test was performed at a speed of 300 mm / min in a constant temperature atmosphere of 23°C to measure the adhesive strength. As above, the adhesive strengths in Examples 1 to 3 and Comparative Examples 1 to 5 are the adhesive strengths at the interface between the ethylene-vinyl alcohol copolymer layer and the adhesive resin layer. The adhesive strength in Comparative Example 6 is the adhesive strength at the interface between the polyester resin layer and the adhesive resin layer.
[0084] [Example 1] <Production of Modified Polyester Elastomer> As shown in Table 1, 100 parts by mass of polyester elastomer A-1, 0.5 parts by mass of B, 0.1 parts by mass of C, and 0.1 parts by mass of X were used, dry blended, and mixed. The mixture was melt-kneaded using a twin-screw extruder (manufactured by Nippon Steel Corporation, TEX25αIII, D=25mmφ, L / D=53) at a set temperature of 180-240°C, a screw rotation speed of 200-400 rpm, and an extrusion rate of 15-30 kg / h, and pellet-shaped modified polyester elastomer was obtained by strand cutting. The degree of swelling of this modified polyester elastomer was measured.
[0085] <Production of laminated molded body> A 5-layer film was produced as a laminated molded product of polyester resin layer / adhesive resin layer made of modified polyester elastomer / ethylene-vinyl alcohol copolymer layer / adhesive resin layer made of modified polyester elastomer / polyester resin layer using a multi-layer film molding machine (Pla Giken Co., Ltd.) with a 320 mm wide 4-type 5-layer multi-manifold type T-die. The temperature of the T-die was set at 250°C, the molding speed was 10 m / min, the cast roll temperature was 30°C, and a film with a total thickness of 400 μm was obtained with the thicknesses of the individual layers being 140 μm / 40 μm / 40 μm / 40 μm / 140 μm. The adhesive strength of the resulting five-layer film was measured.
[0086] The results of the above measurements are shown in Table 1.
[0087] [Examples 2 to 3, Comparative Examples 1 to 5] In the production of the modified polyester elastomer, modified polyester elastomers were obtained in the same manner as in Example 1, except that the ingredients were blended as shown in Table 1, and laminated molded articles were produced in the same manner, and measurements were carried out for each. The results are shown in Table 1.
[0088] [Comparative Example 6] A laminate was produced in the same manner as in Example 1, except that an acid-modified polyethylene "Modic H501E" was used in the adhesive resin layer instead of the modified polyester elastomer, and the adhesive strength was measured. The results are shown in Table 1.
[0089] [Table 1]
[0090] From Table 1, it can be seen that Examples 1 to 3, which are specific examples of the modified polyester elastomer of the present invention, exhibit high adhesion to the ethylene-vinyl alcohol copolymer and the polyester resin layer, while also exhibiting good solvent durability. In contrast, in Comparative Examples 1 and 2 in which the polyalkylene ether glycol segment content of the modified polyester elastomer was lower than the range specified in the present invention, the acid modification rate was low and both the adhesion and solvent durability were poor. In Comparative Examples 3 to 5, in which the content of polyalkylene ether glycol segments in the modified polyester elastomer is higher than the range specified in the present invention, the solvent durability is poor. In Comparative Example 6, in which acid-modified polyethylene was used, no adhesiveness was obtained.< / mfr>
Claims
1. A laminated molded product comprising at least an adhesive resin layer containing a modified polyester-based elastomer and a gas barrier resin layer, The modified polyester-based elastomer is a modified polyester-based elastomer obtained by modifying a polyester-based elastomer consisting of a polyester-polyether block copolymer composed of a hard segment containing an aromatic polyester and a soft segment containing a polyalkylene ether glycol segment with an unsaturated carboxylic acid and / or a derivative thereof, and the content of the polyalkylene ether glycol segment in the modified polyester-based elastomer is 36 to 53 mass %, the adhesive resin layer contains the modified polyester-based elastomer in an amount of 50% by mass or more based on the total components of the adhesive resin layer, The gas barrier resin layer comprises any one selected from an ethylene-vinyl alcohol copolymer and a polyamide-based polymer.
2. 2. The laminate according to claim 1, wherein the gas barrier resin layer is a resin layer containing an ethylene-vinyl alcohol copolymer as a main component.
3. The laminate molded product according to claim 1 or 2, further comprising a polyester-based resin layer, the adhesive resin layer being disposed between the gas barrier resin layer and the polyester-based resin layer.
Citation Information
Patent Citations
Adhesive polymer composition and its manufacturing method
JP2002155135A
Adhesive resin composition and multiple layered laminate structural material
JP2003073506A
Biaxially oriented breathable film, method for producing same and use thereof
JP2009506147A
Modified alicyclic polyester and molding
JP2012193239A
Multilayer film, laminate, air bag, and method for producing laminate
JP2019001163A
